Multi-Level Governance and Industrial Engagement in Renewable Energy Communities: A Pre-Regulatory Study from Lombardy - Maria Garbelli (European Scientific Journal, ESJ, 2025)
This study investigates the early-stage development of renewable energy communities in Italy, focusing on how small and medium-sized industries in the Lombardy region perceived and responded to communication efforts before the full implementation of new regulatory frameworks and economic incentives. The research is based on data collected through a targeted survey conducted among industrial firms. The analysis explores the roles played by national and regional institutions, as well as local public authorities such as municipalities, in shaping awareness and interest in renewable energy participation. A non-parametric statistical test was used to assess the influence of different governance levels on industrial engagement. Results indicate that Local Public Authorities exert a significantly stronger influence on industrial perceptions and willingness to engage in Renewable Energy Communities (REC) than higher-level institutions. In the surveyed sample, 51% of Small and Medium-sized Industries (SMI) reported no or minimal awareness of REC, with 34% expressing no interest in participation, primarily due to limited communication and lack of familiarity. Conversely, the highest awareness levels (up to 26%) were recorded in areas where Local Public Authorities maintained proactive and trust-based communication, such as Lecco–Sondrio, suggesting that localized outreach is notably more effective than top-down regional campaigns. These findings highlight the need for coordinated, place-based governance strategies that reinforce the role of local actors in energy transition initiatives. Municipalities and similar authorities may serve as crucial intermediaries, translating national strategies into meaningful local action. By capturing industry perceptions prior to the implementation of national Renewable Energy Communities incentives, this study offers a unique and unbiased perspective on how businesses naturally engage with different levels of governance. It contributes to the broader understanding of how trust and proximity influence participation in sustainable energy systems.